2021
DOI: 10.3390/nu13124546
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obesity Class on the Energetics and Mechanics of Walking

Abstract: Higher mass-normalized net energy cost of walking (NetCw/kg) and mechanical pendular recovery are observed in obese compared to lean adults. This study aimed to investigate the effect of different classes of obesity on the energetics and mechanics of walking and to explore the relationships between body mass, NetCw/kg and gait mechanics by using principal component analysis (PCA). NetCw/kg and gait mechanics were computed in severely obese (SOG; n = 18, BMI = 40.1 ± 4.4 kg·m−2), moderately obese (MOG; n = 17, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The data displayed in Figure 1 Published data on the impact of BMI or body fat on the metabolic cost of walking are inconsistent. A higher net Cw or metabolic rate in adults with obesity has been reported in some studies (Browning et al, 2006;Browning & Kram, 2005;Fernandez Menendez et al, 2020;Primavesi et al, 2021) but not others (Bode et al, 2020;Browning et al, 2013; , 2009). One study actually reported a lower relative VȮ 2 (mL/kg/min) during walking in females with severe obesity compared to relatively lean females (Farrell et al, 1985).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The data displayed in Figure 1 Published data on the impact of BMI or body fat on the metabolic cost of walking are inconsistent. A higher net Cw or metabolic rate in adults with obesity has been reported in some studies (Browning et al, 2006;Browning & Kram, 2005;Fernandez Menendez et al, 2020;Primavesi et al, 2021) but not others (Bode et al, 2020;Browning et al, 2013; , 2009). One study actually reported a lower relative VȮ 2 (mL/kg/min) during walking in females with severe obesity compared to relatively lean females (Farrell et al, 1985).…”
Section: Discussionmentioning
confidence: 80%
“…In the earlier study (Fernandez Menendez et al, 2019), net Cw was not different between groups with different mean BMI (33.8 kg/m 2 vs. 21.9 kg/ m 2 ) at the four slowest speeds, but was only significantly greater in the higher-BMI group at the fastest walking speed (1.67 m/s). A third study (Primavesi et al, 2021) from this group, that used pooled data from the first two studies along with additional participants, found that net Cw in individuals with grade II or III obesity (BMI ≥ 35 m/ kg 2 ; mean = 40.1 m/kg 2 ) was 15% higher than net Cw in individuals with a BMI in the normal-weight range (BMI 18.5-24.9 kg/m 2 ; mean = 22.0 m/kg 2 ) but nonsignificantly 6% higher than individuals with grade I obesity (BMI 30-34.9 m/kg 2 ; mean = 32.2 kg/m 2 ). The authors posited that the degree of obesity influences net Cw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine obese (OB) (six female, 8.7 ± 0.5 years, 1.38 ± 0.04 m, 44.4 ± 6.3 kg, and 24.1 ± 3.50 kg/m 2 ) and eight non-obese (Non-OB) (four female, 7.4 ± 0.7 years, 1.31 ± 0.08 m, 26.6 ± 2.1 kg and 16.4 ± 1.40 kg/m 2 ) children took part. The sample size of eight participants per group was calculated based on the recovery data of the study byPrimavesi et al (2021), using α of 0.05 and power of 0.90. The participants were chosen by convenience.…”
mentioning
confidence: 99%